TOXICITY AND IMMUNOMODULATORY ACTIVITY OF FRACTIONS OF HIBISCUS SABDARIFFA LINN (FAMILY MALVACEAE) IN ANIMAL MODELS - Fakeye, Titilayo (African Journal of Traditional, Complementary and Alternative Medicines, 2008)
This study evaluated immunomodulatory properties and the sub-acute toxicity profile of two fractions of the aqueous alcoholic extract of the dried calyx of Hibiscus sabdariffa in experimental animals. Immunomodulatory activity was evaluated using red blood cell-induced immunostimulation. The fractions were not found to be toxic after 7-day administration, though there was severe weight loss with the residual water-soluble fraction (RWSF) and weight gain with the ethyl acetate soluble fraction (EAC). The EAC exhibited a significant dose-dependent immunostimulation (p<0.05) higher than that observed for levamisole (positive control). The residual water-soluble fraction exhibited immunostimulatory activity at 100mg/kg body weight. The two fractions caused a significant reduction in production of tissue necrosis factor – alpha and an increase in interleukin 10 (IL-10).